2006
DOI: 10.1037/0022-0663.98.4.732
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic review of social, self-concept, and behavioral outcomes of peer-assisted learning.

Abstract: Meta-analysis was used to examine social, self-concept, and behavioral effects of peer-assisted learning (PAL) interventions with elementary school students. An electronic search of PsycINFO and ERIC databases resulted in 36 relevant PAL studies. Overall, effect sizes were small to moderate across the 3 outcome variable domains. Both social and self-concept outcomes were positively correlated with academic outcomes. Specific PAL components-student autonomy, individualized evaluation, structured student roles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
122
2
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(149 citation statements)
references
References 88 publications
12
122
2
13
Order By: Relevance
“…A recent meta-analysis examining the socio-emotional outcomes of PAL interventions with elementary school students found that such programs can result in positive social, self-concept and behavioural outcomes. Furthermore, significant positive associations were established between these social and self-concept outcomes and students' academic achievement (Ginsburg-Block et al, 2006). Similar findings were established in Tariq's (2005) study examining feedback on PAL from 112 bioscience undergraduates.…”
Section: Additional Benefits Of Palsupporting
confidence: 69%
See 1 more Smart Citation
“…A recent meta-analysis examining the socio-emotional outcomes of PAL interventions with elementary school students found that such programs can result in positive social, self-concept and behavioural outcomes. Furthermore, significant positive associations were established between these social and self-concept outcomes and students' academic achievement (Ginsburg-Block et al, 2006). Similar findings were established in Tariq's (2005) study examining feedback on PAL from 112 bioscience undergraduates.…”
Section: Additional Benefits Of Palsupporting
confidence: 69%
“…These outcomes include social development, self-concept and positive changes in attitude (Ginsburg-Block, Fantuzzo & Rohrbeck, 2006;Fantuzzo & Ginsburg-Block, 1998). This is important when we consider findings from research studies that have shown that links exist between academic achievement and factors such as self-esteem, self-concept, friendship and social skills (Eccles, Roeser, Wigfield & Freedman-Doan, 1999;Parker, Rubin, Price & DeRosier, 1995).…”
Section: Additional Benefits Of Palmentioning
confidence: 99%
“…A recent meta-analysis examining the socio-emotional outcomes of PAL interventions with elementary school students found that such programs can result in positive social, self-concept and behavioural outcomes. Furthermore, significant positive associations were established between these social and self-concept outcomes and students' academic achievement (Ginsburg-Block et al, 2006). Similar findings were established in Tariq's (2005) study examining feedback on PAL from 112 bioscience undergraduates.…”
Section: Additional Benefits Of Palsupporting
confidence: 69%
“…Similar findings for the above variables, especially for autonomous structural elements that give the choice to the students, have been shown for the impact of peer tutoring or groups of three for the process of learning elements such as self-concepts and behaviour [6].…”
Section: Literature Reviewsupporting
confidence: 62%